PENGARUH UKURAN PERUSAHAAN, SOLVABILITAS DAN KOMITE AUDIT TERHADAP AUDIT DELAY - Muhammad Rizal Saragih (Universitas Pamulang, 2018)
The problems that will be discussed in this journal regarding the relationship between the business entity, the solvency of audit delay. The research method used in this study uses secondary data. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2013, 2014, 2015 and 2016. The sampling method in this study was purposive sampling. The criteria of the company being sampled are companies that publish audited financial statements for four consecutive years and use the rupiah currency, so the total number of samples in this study is 100 data. Independent variables in this study are company size, solvability and audit committee, variables dependent inthis study is audit delay. The data analysis technique used is multiple linear regression.The results of the analysis show that the solvability variable has a significant effect on audit delay. While the variable size of the company and the audit committee does not have a significant effect on audit delay.